Targeted Marine Phytoplankton Supplementation Improves Recovery During Intensified Training. (29th May 2020) - Wilson, Jacob; Stefan, Matthew; Sharp, Matthew; Book, Nicholous; Reber, Dallen; Gheith, Raad; Ottinger, Charlie; Lowery, Ryan; Juturu, Vijaya
Abstract: Objectives: The purpose of this study was to investigate marine phytoplankton supplementation (Microalgae Tetraselmis chuii, Oceanix™, OCX) that is rich in antioxidant enzymes, essential fatty acids, vitamins, amino acids and minerals on Explosive Strength (ES), and Immune Function during short term intensive training. Methods: Trained male and female subjects were randomly divided into a microcrystalline cellulose based placebo (PLA, ) or Oceanix™ (OCX) (25 mg per day) condition for 14 days. Subjects were tested at baseline and then placed on an intensified based resistance training protocol using multiple sets to volitional failure over the course of 5 days and retested 24 and 48 hours following. Explosive strength, measured as rate of force development during an isometric mid thigh pull was assessed. Immune function was determined using salivary immunoglobulin-A (IgA). Repeated measures ANOVA and Tukey post hoc analysis were used to assess differences. Results: Explosive Strength was significantly lower at 24 (-62%) and 48 (-78%) hours in the PLA but not OCX compared to pre levels ( P < 0.05). Additionally, the absolute mean difference in Explosive Strength from Pre to 48hr-Post was significantly lower in PLA compared to OCX ( P < 0.05), indicating greater recovery in OCX. Forty-eight hour post IgA levels decreased compared to Pre ( P < 0.05, −178%) in the PLA but not OCX group. Conclusions: Targeted marine phytoplankton supplementation (Oceanix™, OCX) improves short term recovery from short term intensive training. Funding Sources: Lonza.